Profil Asam Lemak dan Triasilgliserol Berantai Sedang (MCFA) dalam Kelapa Segar dan Santan (Cocos nucifera L.) - Rita Hayati (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Fatty Acids Profile and Medium Changes Fatty Acids (MCFA) on Coconut Fresh and Coconut Milk (Cocos nucifera L.)ABSTRACT. This study was conducted to determine the fatty acids profile and medium changes fatty acids on coconut fresh and coconut milk. The fatty acids content of coconut fresh and coconut milk of saturated fatty acids (120.88- 84%) consist of C6:0, C8:0, C10:0, C12:0, C14:0, C16:0, C18:0. The monounsaturated fatty acids present was palmitoleic acid (C6:1c9) and oleic acid (C18:1n9) amounting to 15.7-16.2%, respectively. While linoleic (C18:2n6) was the major polyunsaturated fatty acids, amounting to 2.20-3.40%. The total medium changes fatty acids (MCFA) in coconut fresh and coconut milk were 70.0% and 67.5%.